Editorial: From rationality to emotionality - Wit Pasierbek (Jesuit University Ignatianum in Krakow, 2010)
The two previous issues of "The Horizons of Education" concerned the matters of rationality and thinking. They are the fundamental factors of human constitution which allow man to lead a sensible life. However, as we noticed, rationality and the process of thinking are not always used properly; furthermore, along with the deep involvement of the whole psycho-physical sphere, serious emotional upsets arise not infrequently evoking a strong response in man's attitudes. But it can be different: symbiosis between the rational and feelings, the rational and emotions brings about the ability to breathe the whole of oneself, every fibre of one's own being. It is then that one can talk about "having a liking for life" and its proper quality. The only problem lies in the ability to find this "golden mean" for coexistence, collaboration. The Editorial Team aimed at making this transition "from rationality to emotionality" which became the focus of this issue of the magazine. The point is that, on one hand, man would not suppress his emotions which determine his dynamism and vitality and which sometimes may lead him astray, and one the other hand, this sphere of emotionality would be somehow managed by reason. It also happens that feelings, emotions are not realized, and only manifest their existence and, in that case, it is harder to control this rationally. Naturally, it is difficult to find a concrete and explicit recipe for such functioning, though it is certainly possible.